Key design elements of successful acute ischemic stroke treatment trials - Yperzeele, Laetitia; Shoamanesh, Ashkan; Venugopalan, Y. V.; Chapman, S.; Mazya, Michael V.; Charalambous, Marina; Caso, V.; Hacke, Werner; Bath, Philip; Koltsov, I. (My University, 2023)
Purpose We review key design elements of positive randomized controlled trials (RCTs) in acute ischemic stroke (AIS) treatment and summarize their main characteristics. Method We searched Medline, Pubmed and Cochrane databases for positive RCTs in AIS treatment. Trials were included if (1) they had a randomized controlled design, with (at least partial) blinding for endpoints, (2) they tested against placebo (or on top of standard therapy in a superiority design) or against approved therapy; (3) the protocol was registered and/or published before trial termination and unblinding (if required at study commencement); (4) the primary endpoint was positive in the intention to treat analysis; and (5) the study findings led to approval of the investigational product and/or high ranked recommendations. A topical approach was used, therefore the findings were summarized as a narrative review. Findings Seventeen positive RCTs met the inclusion criteria. The majority of trials included less than 1000 patients (n = 15), had highly selective inclusion criteria (n = 16), used the modified Rankin score as a primary endpoint (n = 15) and had a frequentist design (n = 16). Trials tended to be national (n = 12), investigator-initiated and performed with public funding (n = 11). Discussion Smaller but selective trials are useful to identify efficacy in a particular subgroup of stroke patients. It may also be of advantage to limit the number of participating countries and centers to avoid heterogeneity in stroke management and bureaucratic burden. Conclusion The key characteristics of positive RCTs in AIS treatment described here may assist in the design of further trials investigating a single intervention with a potentially high effect size.
Keywords: Acute stroke care; Acute stroke therapy; Randomized controlled trials; Stroke; Stroke research; Trial design